Stress from sports initiation to the professionalism: an exploratory analysis of the trajectory of professional football athletes - Aroni, Andre Luis; Bagni, Guilherme; Bocchio, Giovanni Luchetti; Filho, Edson; Machado, Afonso Antonio [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2019)
In recent years, sports initiation have been the object of study of numerous works inside the international literature, as well as the career transition. However, much of the career transition focuses on the end of the professional career. Thus, the objective of the present study was to analyze the trajectory of football players in the process of sports initiation to professionalization, observing the sources of stress and coping in each category transition. A total of 27 professional players participated in this descriptive and exploratory study. An interview scrip with fifteen questions, based on the instruments of Gomes (2011) and Stambulova and collaborators (2009), was used to gather data. Numerous sources of stress (e.g., parents' behavior, injuries, stronger athletes) and related coping strategies (e.g., problem-focused coping, emotion-focused coping) were identified by the players throughout the process of sports initiation and professionalization. The majority of coping strategies consisted of problem-focused approaches that parallel the different stress demands encountered by the athletes over the course of their career development. As final considerations, the study contributes to the fact that coaches and leaders of sports initiation can be attentive to the demands presented, besides the usual physical, technical and tactical questions.
Keywords: Stress; Psychological; Adaptation; Football